Global research activity on olfactory marker protein (OMP): a bibliometric and visualized analysis - Ab Aziz, Salmi; Mohd Nasir, Mohd Hamzah; Jusoh, Ab Rashid; Azman, Khairunnuur Fairuz; Ismail, Che Aishah Nazariah; Ahmad, Asma Hayati; Othman, Zahiruddin; Zakaria, Rahimah (Cell Press, 2024)
Olfactory marker protein (OMP) is extensively studied in mature olfactory receptor neurons (ORNs) for understanding olfaction physiology. However, no bibliometric analysis on this topic exists. We conducted a bibliometric analysis of OMP research articles, wherein the publication count was assessed by year, country, journal, and author, collaboration by country, and productivity of the authors. Additionally, key terms and research themes were identified. Using the search phrase “olfactory marker protein” in Scopus, we retrieved 691 original research articles by 2487 authors since 1974. Publications showed an increasing trend, with the United States leading in quantity and collaboration. Our thematic map highlights “Olfactory bulb, regeneration, olfactory” as the primary research domain, while “olfaction, olfactory sensory neuron, glomerulus” and “olfactory receptor neurons, apoptosis, olfactory dysfunction” emerge as essential future research topics. These bibliometric findings offer insights into the global OMP research landscape, guiding researchers in potential collaborations and intriguing future research fields.